2019
DOI: 10.1088/1361-6463/ab2fea
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven flexible 2D plasmonic structure based on a nematic liquid crystal

Abstract: A novel 2D active plasmonic grating based on liquid crystal (LC) infiltration is demonstrated and theoretically analyzed, by combining the plasmonic properties of the gold nanostructure and the optical properties of the liquid crystal. In this structure, a thin layer of E7 liquid crystal was typically injected onto a gold nanostructure, deposited on a polydimethyl siloxane substrate, using nanoimprint lithography method. The surface plasmon resonance of the fabricated plasmonic structure can be controlled by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…3(a), (b) and (c), respectively. The excitation of the surface lattice resonance (SLR) of these 2D grating structures typically occurs at incidence angles ranging between 50 and 60 degrees [18,19]. In this research, sweeping of the incidence angle showed that a sharp and strong SLR response occurs at an incidence angle of 58 degrees.…”
Section: Resultsmentioning
confidence: 85%
“…3(a), (b) and (c), respectively. The excitation of the surface lattice resonance (SLR) of these 2D grating structures typically occurs at incidence angles ranging between 50 and 60 degrees [18,19]. In this research, sweeping of the incidence angle showed that a sharp and strong SLR response occurs at an incidence angle of 58 degrees.…”
Section: Resultsmentioning
confidence: 85%
“…For this purpose, the poly-dimethylsiloxane (PDMS) substrate was patterned as 2D substrate and covered by gold layer of 35 nm thickness to keep the valley part of the sample and reach to the patterned nanostructure after gold and also NiFe covered layer. The same fabrication process was used in our previous works [13,14]. The geometrical parameters of this sample are shown in Figure 1 (b) in a representative SEM image of the 2D plasmonic grating in a simple cubic structure with 1.2 µm unit cell, 2.84µm × 2.84 µm grating period, 302 nm in length and 30 nm in the diameter for gold nanowire.…”
Section: Experimental Workmentioning
confidence: 99%
“…Actually, different groups have been focused on the enhancement of the magneto-optical activity of the systems [7][8][9][10][11] as well as a few have been concentrated on the active control of the plasmon resonance [12] of such a system. In order to expand the area of research in active plasmonics and to complement our previous works that are based on electro-optical [13] and all-optical [14] effects in two dimensional (2D) plasmonic grating, an idea of improving the response of that system and controlling the plasmonic excitations as well as detecting the switching process is demonstrated by us, using the magneto-optical effects. Since our 2D plasmonic structure considered in here is a periodic array of gold nanoparticles, it supports surface lattice resonance (SLR) that results from the coupling of the diffractive waves and the localized plasmon resonance associated with individual nanoparticles at a wavelength comparable to their period.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that our plasmonic structure is formed by gold nano arrays that are arranged in a wavelength scale array, in which the array period is comparable to the wavelength of the particle plasmon resonance and therefore two important hybridized modes can exist: The narrow diffracted orders (DOs) and Localized surface plasmons resonance (LSPRs) in far-field measurements 21 . Furthermore, when the LSPRs associating with individual nano rods couple the diffracted waves propagating in planar surface, an exciting phenomenon can take place, also referred to as surface lattice resonance (SLRs) 3,20 .…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of 2D plasmonic grating is successfully completed using nanoimprint lithography method. Details of this method and the fabrication process to produce plasmonic structure are described in our previous work 3 . After deposition of the gold layer and attaining two dimensional (2D) plasmonic structure, a thin film of 8-Hydroxypyrene-1,3,6-trisulfonic (HPTS) is coated on, which allows the definition of switching under UV radiation that supposed leading to a good tuning of the plasmonic properties of the structure.…”
Section: Experimental Partmentioning
confidence: 99%